A new species of Noblella (Amphibia: Strabomantidae) from the Río Manduriacu Reserve on the Pacific slopes of the Ecuadorian Andes. Issue 1 (1st January 2020) - Reyes-Puig, Carolina; Maynard, Ross J.; Trageser, Scott J.; Vieira, José; Hamilton, Paul S.; Lynch, Ryan; Culebras, Jaime; Kohn, Sebastián; Brito, Jorge; Guayasamin, Juan M.
ABSTRACT: With the third most biodiverse amphibian fauna in the world, Ecuador has bolstered this claim with a particularly high rate of species descriptions in recent years. Many of the species being described are already facing anthropogenic threats despite being discovered within privately protected reserves in areas previously not sampled. Herein we describe a new species of terrestrial frog in the genus Noblella from the recently established Río Manduriacu Reserve, Imbabura, Ecuador. Noblella worleyae sp. nov. differs from its congeners by having a dorsum finely shagreen; tips of Fingers I and IV slightly acuminate, Fingers II and III acuminate, without papillae; distal phalanges of the hand slightly T-shaped; absence of distinctive suprainguinal marks; venter yellowish-cream with minute speckling and throat with irregular brown marks to homogeneously brown. We provide a detailed description of the advertisement call of the new species and present an updated phylogeny of the genus Noblella . In addition, we emphasize the importance of the Río Manduriacu Reserve as a conservation area to threatened fauna. Ecuador es el tercer país más diverso en anfibios, y la descripción de especies en los últimos años ha aumentado considerablemente, evidenciando la presencia de nuevas especies en áreas privadas protegidas, muchas de las cuales enfrentan amenazas antropogénicas. Aquí describimos una nueva especie de rana terrestre del género Noblella de la vertiente pacífica de los Andes ecuatorianos en la Reserva Río Manduriacu, provincia de Imbabura. Noblella worleyae sp. nov. se diferencia de sus congéneres por la presencia de un dorso finamente granular, puntas de los dedos I y IV ligeramente acuminados, dedos II y III acuminados, sin papila; falanges distales de la mano ligeramente en forma de T; ausencia de marcas distintivas suprainguinales; vientre crema amarillento moteado con diminutos puntos , garganta con marcas cafés irregulares a homogéneamente café. Proporcionamos una descripción detallada del canto de la nueva especie y presentamos una filogenia actualizada del género Noblella . Además, enfatizamos la importancia de la Reserva Río Manduriacu como un área de conservación para fauna amenazada.